Odpowiedzi

2010-02-22T20:36:27+01:00
Mg(OH)₂ + H₂SO₄ = MgSO₄ + 2H₂O
3NaOH + H₃PO₄ = Na₃PO₄ + 3H₂O
2010-02-22T20:39:58+01:00
Mg(OH)2 + H2SO4 ---> MgSO4 + 2H2O

3NaOH + H3PO4 ---> Na3PO4 + 3H2O
Najlepsza Odpowiedź!
2010-02-22T20:45:50+01:00
A) Mg (OH)2 + H2SO4 -----> MgSO4 + 2H2O
(teraz te indeksy takie jak 2+ beda musialy byc na gorze )
Mg 2+ + 2OH- + 2H+ + SO4- ----> Mg2+ + SO4 2- + 2H2O
2OH- + 2H+ -----> 2H2O |:2
OH- + H+ -----> H2O
b)3NaOH + H3PO4 -----> Na3PO4 + 3H2O
3Na+ + 3OH- + 3H+ + PO4 3- -----> 3Na+ + PO4 3- + 3H2O
3OH- + 3H+ ----------> 3H2O |:3
OH- + H+ -------------> H2O
2 4 2